The psychopathological and psychosocial outcome of early-onset schizophrenia: Preliminary data of a 13-year follow-up - Mehler-Wex Claudia; Kreiker Susanne; Reichert Andreas; Warnke Andreas (BMC, 2008)
Abstract Background Relatively little is known about the long-term psychopathological and psychosocial outcome of early-onset schizophrenia. The existing literature describes more severe courses of illness in these patients compared with adult-onset schizophrenia. This article reports preliminary data of a study exploring the outcome of early-onset schizophrenia 13.4 years (mean) after first admission. Predictors for interindividual outcomes were investigated. Methods We retrospectively assessed 27 former patients (mean age at first admission 15.5 years, SD = 2.0) that were consecutively admitted to the Department of Child and Adolescent Psychiatry at the University of Wuerzburg between 1990 and 2000. A multidimensional approach was chosen to assess the outcome consisting of a mail survey including different questions about psychopathological symptoms, psychosocial parameters, and standardized self-reports (ESI and ADS). Results Concerning the psychopathological outcome, 22.2% reported having acute schizophrenic symptoms. Almost one third (30.8%) described symptoms of depression and 37.0% reported having tried to commit suicide or seriously thought about it. 77.8% of the former patients were still in outpatient treatment. Compared to the general population, the number of patients without a school graduation was relatively high (18.5%). Almost half of participants still live with their parents (48.1%) or in assisted or semi-assisted living conditions (33.3%). Only 18.5% were working in the open market. Conclusion Schizophrenia with an early onset has an unfavourable prognosis. Our retrospective study of the psychopathological and psychosocial outcome concludes with a generally poor rating.